Modification of Polymethyl Methacrylate Based on Hybrid CdSe/ZnS AND CdSe/CdS/ZnS Quantum Dots - Ishankulov A.F; Shamilov R.R; Khalilov K.F; Galyametdinov Yu.G; Mukhamadiev N.K (Genius Journals, 2022)
CdSe quantum dots obtained by the colloid method were stabilized with oleic acid and their optical properties were studied. By growing a ZnS shell on the surface of CdSe nanoparticles, a hybrid CdSe/ZnS “core-shell” nanoparticle was synthesized. At the same time, the luminescence quantum yield increased from 1.5 to 19%. As a result, the luminescence spectral wavelength peak of the CdSe/ZnS quantum point shifted to a shorter region. On the basis of a semiconductor material, a hybrid CdSe/ZnS quantumsized (1-10 nm) hybrid of cadmium selenide with a “core-shell” structure was synthesized. The absorption and luminescence spectra of quantum dots were studied and quantum yield was calculated theoretically. The values of the theoretical and experimental dimensions of CdSe nanocrystals were studied comparatively
Keywords: Quantum dots; colloid synthesis; cadmium selenide; luminescence